A multifaceted strategy to improve recombinant expression and structural characterisation of a Trypanosoma invariant surface protein - Sülzen, Hagen; Votrubova, Jitka; Dhillon, Arun; Zoll, Sebastian (Scientific reports, 2022)
Identification of a protein minimal fragment amenable to crystallisation can be time- and labour intensive especially if large amounts are required and the protein has a complex fold and functionally important post-translational modifications. In addition, a lack of homologues and structural information can further complicate the design of a minimal expression construct. Recombinant expression in E. coli promises high yields, low costs and fast turnover times, but falls short for many extracellular, eukaryotic proteins. Eukaryotic expression systems provide an alternative but are costly, slow and require special handling and equipment. Using a member of a structurally uncharacterized, eukaryotic receptor family as an example we employ hydrogen-deuterium exchange mass spectrometry (HDX-MS) guided construct design in conjunction with truncation scanning and targeted expression host switching to identify a minimal expression construct that can be produced with high yields and moderate costs.
Keywords: Membrane Proteins; membránové proteiny; Protein Conformation; Deuterium Exchange Measurement; Hydrogen Deuterium Exchange-Mass Spectrometry; Escherichia coli; vodík-deuteriová výměna; vodík/deuteriová výměna a hmotnostní spektrometrie; Trypanosoma; konformace proteinů